Impact of Globalization on Human Rights in Developing Countries: Connecting the Dots towards the SDGs - Hafiz, Nusrat; Sabrina, Farin (Society & Sustainability, 2023)
This study focuses on the complex interaction between globalization and human rights. The study uses a multifaceted approach to analyze the possible overlaps and conflicts between globalization and human rights to find ways to lessen negative effects and maximize good ones. The research intends to identify the gaps and possibilities of implementing the Sustainable Development Goals (SDGs) by looking at the particular difficulties encountered by developing countries. The study reveals the intricate interactions between globalization and human rights using data from several case studies as well as a thorough examination of the literature. It identifies several significant impact areas, such as labor rights, access to healthcare and education, environmental sustainability, gender equality, and the defense of indigenous peoples’ rights. Additionally, the study evaluates how governments, civil society, international organizations, and other stakeholders are addressing the adverse effects of globalization on human rights and sustainable development. The paper unleashes mitigating factors and emphasizes the obligations of the many UN stakeholders to defend human rights and assist in the achievement of the SDGs. By resolving these issues, developing nations may more effectively take advantage of globalization’s potential advantages while defending human rights and pursuing sustainable development objectives within the SDG framework. One of the key limitations of this paper is the lack of access to achieving primary data and the generalization of the concept itself. The impact of globalization has a deeper and specific scope of discussion.